2022
DOI: 10.1038/s41598-022-06003-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rare earth elements on bacteria in rhizosphere, root, phyllosphere and leaf of soil–rice ecosystem

Abstract: The effects of rare earth mining on rice biomass, rare earth element (REE) content and bacterial community structure was studied through pot experiment. The research shows that the REE content in rice roots, shoots and grains was significantly positive correlated with that in soil, and the dry weight of rice roots, shoots and grains was highly correlated with soil physical and chemical properties, nutrient elements and REE contents; The exploitation of rare earth minerals inhibited a-diversity of endophytic ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…DNA concentration and purity were measured using the micro ultraviolet–visible spectrophotometer, NanoDrop2000, and then stored in a refrigerator at − 20 °C for subsequent 16S rRNA gene analysis. Experimental methods were according to Zhang et al 30 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DNA concentration and purity were measured using the micro ultraviolet–visible spectrophotometer, NanoDrop2000, and then stored in a refrigerator at − 20 °C for subsequent 16S rRNA gene analysis. Experimental methods were according to Zhang et al 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Sample data that were too small were removed and UNITE database was used for species annotation. The experimental method was according to Zhang et al 30 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,48 This effect on the snail gut microbiome was not directly due to the fact that the snails were exposed indirectly to the REEs. Previous studies have shown that REEs directly affected the bacteria in the phyllosphere and leaf of a soil−rice system 49 and changed the metabolites in the leaves of plants. 50 However, our study, for the first time, revealed the indirect effects of REEs on microbiota through the food chain.…”
Section: Impacts Of Dietarymentioning
confidence: 99%